Plant and animal lectines as modulators of mgmt and marp gene expression in vitro - Macewicz, L.L.; Lylo, V.V.; Karpova, I.S.; Kotsarenko, K.V.; Ruban, T.A.; Lukash, L.L. (Фактори експериментальної еволюції організмів, 2014)
Aims. Previously for the first time we have studied the ability of lectins to influence the processes of mutagenesis and antimutagenesis in different test systems. The aim of present study was to examine the effect of panel of lectins on the MGMT and MARP expression levels in tumor and non-tumor mammalian cells in vitro. Methods. Standard cell cultivation methods and Western blot analysis were used. Results. The influence of plant and animal lectins (perk egg lectin, lentil seeds lectin and elderberry bark lectin) on expressiom of proteins recognized by anti-MGMT monoclonal antibodies (MGMT and MARP) on stable and destabilized human non-tumor and tumor-derived cell lines was studied. Conclusions. Studied lectins are able to modulate the expression of MGMT and MARP. The influence of SNA-I on MARP and MGMT expression levels depends on origin and genomic stability of cell line. SNA-I is perspective for further study as potential drug in anti-tumor therapy optimization schemes.

Key words: MGMT expression, MARP expression, lectins, NiCl2, cell lines.